A general and practical Ni-catalyzed C–H perfluoroalkylation of (hetero)arenes. Issue 47 (23rd May 2019) - Zhang, Shaoke; Rotta-Loria, Nicolas; Weniger, Florian; Rabeah, Jabor; Neumann, Helfried; Taeschler, Christoph; Beller, Matthias
Abstract : A direct perfluoroalkylation of (hetero)arenes using the air- and moisture-stable complex (dppf)Ni( o -tol)Cl was developed (23 examples) which allows for the synthesis of various fluorinated products and tolerates sensitive functional groups including aldehydes, free amino groups and several heterocycles. Abstract : A direct perfluoroalkylation of (hetero)arenes using the air- and moisture-stable complex (dppf)Ni( o -tol)Cl was developed (23 examples). The novel procedure allows for the synthesis of various fluorinated products and tolerates sensitive functional groups including aldehydes, free amino groups and several heterocycles.